2011
DOI: 10.1186/cc10556
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin-based versus conventional heparin anticoagulation for postcardiotomy extracorporeal membrane oxygenation

Abstract: IntroductionExtracorporeal membrane oxygenation (ECMO) after cardiac operations (postcardiotomy) is commonly used for the treatment of acute heart failure refractory to drug treatment. Bleeding and thromboembolic events are the most common complications of postcardiotomy ECMO. The present study is a retrospective comparison of the conventional heparin-based anticoagulation protocol with a bivalirudin-based, heparin-free protocol. Endpoints of this study are blood loss, allogeneic blood product use, and costs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
265
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(272 citation statements)
references
References 21 publications
4
265
1
2
Order By: Relevance
“…11,14,15 One recent study 16 systematically analyzed a sample of 21 patients receiving bivalirudin during VA postcardiotomy ECMO. Ranucci et al 16 found that bivalirudin can be used safely and effectively to limit bleeding and allogeneic blood product transfusions in these patients, even if a superiority of bivalirudin versus heparin could not be shown. In this retrospective study, patients in the bivalirudin group had longer activated coagulation times, activated partial thromboplastin clotting times, and reaction times at thromboelastography.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,15 One recent study 16 systematically analyzed a sample of 21 patients receiving bivalirudin during VA postcardiotomy ECMO. Ranucci et al 16 found that bivalirudin can be used safely and effectively to limit bleeding and allogeneic blood product transfusions in these patients, even if a superiority of bivalirudin versus heparin could not be shown. In this retrospective study, patients in the bivalirudin group had longer activated coagulation times, activated partial thromboplastin clotting times, and reaction times at thromboelastography.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no reliance on AT for its effect and therefore allows for more consistent use across all age groups and populations. 12 Their selective binding to thrombin and not to other circulating plasma proteins makes pharmacokinetics more predictable. In a recent survey of the ELSO database, DTIs were found to be used by up to 50% of respondents when indicated.…”
Section: Direct Thrombin Inhibitorsmentioning
confidence: 99%
“…In the setting of ECMO, small case reports and single-center retrospective reviews have been generated describing the use of bivalirudin over heparin [77][78][79]80]. One such report from Ranucci et al [80] described the reduced use of platelet and plasma donor products in patients receiving bivalirudin for postcardiotomy ECMO compared to patients receiving UFH.…”
Section: Bivalirudinmentioning
confidence: 99%
“…One such report from Ranucci et al [80] described the reduced use of platelet and plasma donor products in patients receiving bivalirudin for postcardiotomy ECMO compared to patients receiving UFH. Another small case-controlled study from Pieri et al [81] demonstrated less variation in aPTT but no difference in bleeding and thrombotic complications versus UFH.…”
Section: Bivalirudinmentioning
confidence: 99%